A systematic review of alterations in brain activation and intensity following stroke: implications for integration and functional outcomes - Azri, Amirul; Yahya, Noorazrul; Nabilah Ismail, Umi; Ashari, Muhammad Aminuddin; Abdul Manan, Hanani (Frontiers in Neurology, 2025)
BackgroundStroke remains a leading cause of disability, making it critical to understand the underlying neurophysiological mechanisms for effective rehabilitation. Task-based functional Magnetic Resonance Imaging (fMRI) provides valuable insights into brain activation patterns; however, its correlation with clinical evaluations is not yet fully understood. This systematic review aims to explore the relationship between task-based fMRI findings and clinical assessments in stroke patients, comparing them to healthy controls.MethodsUsing the PubMed database and adhering to PRISMA guidelines, we identified and analyzed 11 eligible studies. Total participant is 323 participant with 258 of them is stroke patients and 65 is HC.ResultsResults reveal significant differences in brain activation patterns between stroke patients and healthy controls, with stroke patients displaying compensatory hyperactivation in certain brain regions such as cerebellum, inferior parietal cortex, and contralesional area. Additionally, longitudinal comparisons among stroke patients show notable improvements in activation patterns from baseline to the subacute and chronic stages following rehabilitation. These changes align with enhanced clinical outcomes, suggesting that fMRI may serve as a sensitive biomarker for recovery progress. Importantly, correlations between fMRI results and clinical scores highlight the potential of task-based fMRI to inform and refine rehabilitation strategies.ConclusionThis review underscores the value of integrating fMRI findings into clinical practice to better understand stroke recovery mechanisms. Further research is needed to deepen our understanding of these associations and optimize patient outcomes in stroke rehabilitation.